Systematic Literature Review: Does Kamishibai Improve Literacy Skills in Early Childhood? - Mashadi, Aisya; Fitri, Ruqoyyah; Jannah, Miftakhul; Kristanto, Andi; Rinakit Adhe, Kartika (Perkumpulan Pengelola Jurnal (PPJ) PAUD Indonesia, 2025)
The low level of literacy in Indonesia remains a critical issue in education, particularly at the early childhood level. Literacy at this stage cannot begin directly with the introduction of letters or numbers; it requires approaches aligned with children's developmental needs. One promising method is Kamishibai, a traditional Japanese storytelling technique that combines visual and narrative elements. This study aims to conduct a systematic literature review of research examining the impact of Kamishibai on early childhood literacy skills. A Systematic Literature Review (SLR) was conducted using the PRISMA model, reviewing literature published between 2021 and 2025 from two databases: Google Scholar and Scopus. A total of eight studies met the inclusion criteria, with research conducted in diverse contexts such as Indonesia, Madagascar (Africa), Finland, and Portugal. The findings indicate that Kamishibai effectively enhances early literacy skills, particularly in contextual literacy, basic literacy, and numeracy. It also supports the development of language and cognitive abilities, expression and creativity, communication and collaboration, as well as reading interest in young children.